2018
DOI: 10.1200/jgo.17.00228
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Cervical Cancer Screening and the Cervical Cancer Care Continuum in Rural Guatemala: A Mixed-Method Analysis

Abstract: PurposeCervical cancer is an important cause of mortality in low- and middle-income countries. Although screening technologies continue to improve, systems of care remain fragmented. It is important to better understand factors that affect use of screening services and loss to follow-up along the care continuum.MethodsWe conducted a mixed-methods study of a cytology-based screening program in rural Guatemala. A retrospective electronic chart review was performed on data from all patients from 2013 to 2014. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 32 publications
6
37
0
Order By: Relevance
“…We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS. In concurrence with other studies, our respondents considered CCS as an intervention for STI management (27,(56)(57)(58). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection specifically) and cervical cancer, and similar findings have been reported by other studies (33,52).…”
Section: Discussionsupporting
confidence: 89%
“…We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS. In concurrence with other studies, our respondents considered CCS as an intervention for STI management (27,(56)(57)(58). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection specifically) and cervical cancer, and similar findings have been reported by other studies (33,52).…”
Section: Discussionsupporting
confidence: 89%
“…We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS. In concurrence with other studies, our respondents considered CCS as an intervention for STI management (25,(50)(51)(52). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection specifically) and cervical cancer, and similar findings have been reported by other studies (31,46).…”
Section: Discussionsupporting
confidence: 89%
“…We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS. In concurrence with other studies, our respondents considered CCS as an intervention for STI management (27,(57)(58)(59). A misconception was found concerning the role of cleanliness and hygiene to prevent STIs (HPV infection speci cally) and cervical cancer, and similar ndings have been reported by other studies (33,53).…”
Section: Discussionsupporting
confidence: 89%